Peningkatan Kesejahteraan Masyarakat Desa Temon Kabupaten Ponorogo Dengan Program Bantuan Stimulan Perumahan Swadaya (BSPS) - Haryanto Bagus Saputro; Ririt Iriani Sri Setiawati; Mohammad Wahed (Jurnal Ilmiah Wahana Pendidikan, 2023)
One of the welfare factors is to have a decent residence. One of the government's programs to help the community, especially low-income people, is the self-help housing stimulant assistance program (BSPS) which aims to improve the quality of livable houses for MBR independently. In this BSPS program, researcher as a companion for empowerment facilitators is tasked with assisting the implementation of BSPS in Temon village, Ponorogo regency, which includes the stages of organizing aid recipients, socialization and counseling, identifying self-help, determining work plans, and construction assistance. The purpose of this assistance is to encourage and assist to society so that self-help arises from the government in improving the quality of houses. The result of this dedication, namely the BSPS program, was welcomed by the people of Temon village, Ponorogo Regency, as evidenced by the high value of self-help and mutual cooperation arising from the beneficiary group.